2022
DOI: 10.1111/cen.14690
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal salivary androstenedione and 17‐hydroxyprogesterone levels in healthy volunteers for monitoring treatment efficacy of patients with congenital adrenal hyperplasia

Abstract: Objective: Treatment of congenital adrenal hyperplasia (CAH) patients with glucocorticoids is often challenging since there is a delicate balance between over-and undertreatment. Treatment can be monitored noninvasively by measuring salivary androstenedione (A4) and 17-hydroxyprogesterone (17-OHP). Optimal treatment monitoring requires the establishment of reference values in saliva.Design: A descriptive study.Patients: For this study saliva of 255 healthy paediatric and adult volunteers with an age range of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Diurnal variation in sample concentrations was also noted in testosterone (T), 17α-hydroxyprogesterone (17aOH-P4), dehydroepiandrosterone (DHEA), progesterone (P4) and androstenedione (A4). This circadian variation is well described in the literature for all four of these steroids, although studies do suggest a loss of this rhythm with increasing age [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 58%
“…Diurnal variation in sample concentrations was also noted in testosterone (T), 17α-hydroxyprogesterone (17aOH-P4), dehydroepiandrosterone (DHEA), progesterone (P4) and androstenedione (A4). This circadian variation is well described in the literature for all four of these steroids, although studies do suggest a loss of this rhythm with increasing age [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 58%
“…For example, Javier et al 33 found that androstenedione can predict the progression of Frailty Syndrome in patients with localized breast cancer treated with aromatase inhibitors. Adriaansen et al 34 reported that diurnal salivary androstenedione levels in healthy volunteers for monitoring treatment efficacy of patients with congenital adrenal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with saliva samples collected only before 11:00 h, the difference in age-matched testosterone concentrations with previous studies was reduced emphasizing the importance of specimen collection time. Salivary androgens exhibit diurnal rhythms ( 5 , 8 , 16 , 34 , 35 ) and the magnitude of the fall in testosterone across the day depends on the age and stage of pubertal development ( 11 , 34 , 36 , 37 ). The current study found that, in boys, salivary testosterone concentration showed a very high correlation with salivary A4.…”
Section: Discussionmentioning
confidence: 99%